TBX4 mutations (small patella syndrome) are associated with childhood-onset pulmonary arterial hypertension. Issue 8 (16th April 2013) - Kerstjens-Frederikse, Wilhelmina S; Bongers, Ernie M H F; Roofthooft, Marcus T R; Leter, Edward M; Douwes, J Menno; Van Dijk, Arie; Vonk-Noordegraaf, Anton; Dijk-Bos, Krista K; Hoefsloot, Lies H; Hoendermis, Elke S; Gille, Johan J P; Sikkema-Raddatz, Birgit; et al.
Abstract : Background: Childhood-onset pulmonary arterial hypertension (PAH) is rare and differs from adult-onset disease in clinical presentation, with often unexplained mental retardation and dysmorphic features (MR/DF). Mutations in the major PAH gene, BMPR2, were reported to cause PAH in only 10–16% of childhood-onset patients. We aimed to identify more genes associated with childhood-onset PAH. Methods: We studied 20 consecutive cases with idiopathic or heritable PAH. In patients with accompanying MR/DF (n=6) array-comparative genomic hybridisation analysis was performed, with the aim of finding common deletion regions containing candidate genes for PAH. Three patients had overlapping deletions of 17q23.2. TBX2 and TBX4 were selected from this area as candidate genes and sequenced in all 20 children. After identifying TBX4 mutations in these children, we subsequently sequenced TBX4 in a cohort of 49 adults with PAH. Because TBX4 mutations are known to cause small patella syndrome (SPS), all patients with newly detected TBX4 mutations were screened for features of SPS. We also screened a third cohort of 23 patients with SPS for PAH. Results: TBX4 mutations (n=3) or TBX4 -containing deletions (n=3) were detected in 6 out of 20 children with PAH (30%). All living patients and two parents with TBX4 mutations appeared to have previously unrecognised SPS. In the adult PAH-cohort, one TBX4 mutation (2%) was detected. Screening in the cohort of (predominantly adult) SPS patients revealed no PAH. Conclusions: These data indicate that TBX4 mutations are associated with childhood-onset PAH, but that the prevalence of PAH in adult TBX4 mutation carriers is low.